Perbedaan Efektivitas Pendidikan Kesehatan Gigi Menggunakan Media Ular Tangga dan Busybook terhadap Pengetahuan Kesehatan Gigi Anak - Wowor, Vonny N. S.; Wicaksono, Dinar A.; Apridinda, Engilica (e-GiGi, 2025)
Abstract: Around 3.5 billion people worldwide face dental health problems, primarily due to a lack of knowledge about the importance of dental care. Therefore, dental health education, especially for children, is crucial. This study was conducted at GMIM Tateli Elementary School, Pineleng District, Minahasa Regency, North Sulawesi Province. The aim of this research was to determine the difference in the effectiveness of dental health education using Snakes and Ladders and Busybook media on children's dental health knowledge. This study employed a quasi-experimental method with a pretest and posttest design involving 32 children aged 6-8 years. The Wilcoxon and Mann-Whitney tests were used for analysis. The Wilcoxon test results for Snakes and Ladders and Busybook media showed a significance value of p = 0.001 (p < 0.05), indicating statistical significance. The Mann-Whitney test showed a significance value of p = 0.048 (p < 0.05), also indicating statistical significance. The conclusion of this study is that dental health education using Snakes and Ladders and Busybook media can improve elementary school children's dental health knowledge, with Snakes and Ladders being more effective than Busybook. Keywords: dental health education; snakes and ladders; busybook